Nanotechnology and nanomedicine in diabetes - Le, Lan-Anh; Hunter, Ross J.; Preedy, Victor R. (Taylor & Francis, 2012)
"Understanding the importance of nanosciences is somewhat problematic as a great deal of text can be rather technical in nature with little consideration to the novice. In this book information is readable as it has sections for the novice and expert alike. Each chapter has an abstract, "key facts", and a "mini-dictionary" of key terms and phrases within each chapter. Each chapter has a summary in point form The book covers for example, introductions to the field, lipid matrix nanoparticles, atomic force microscopy, characterization of tissues at the nanometer scale, antisense oligonucleotides, carbon nanotubes, , nanocomposites, nanorods, carbon nanomaterials, nanolabeled diabetogenic, nanofiber wound dressings, and nanotechnology footsocks"--Provided by publisher